2015
DOI: 10.1111/jth.13052
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin K antagonists' use and fracture risk: results from a systematic review and meta‐analysis

Abstract: use and fracture risk: results from a systematic review and meta-analysis. J Thromb Haemost 2015; 13: 1665-75.Summary. Background: Although vitamin K antagonists (VKAs) lower serum values of bone deposition markers, the link with osteoporosis and fractures remains controversial. Objectives: To assess whether the use of VKAs is associated with an increased prevalence and/or incidence of osteoporosis, fractures, or lower bone mineral density (BMD) values. Methods: We conducted a systematic PubMed and EMBASE lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 38 publications
2
41
0
Order By: Relevance
“…We thank Zhao et al [1] for their careful reading of our recently published meta-analysis [2], in which we assessed the potential relationship between vitamin K antagonists (VKAs) and both bone mineral density and fracture risk, and for their thoughtful comments. The authors raise the following five concerns regarding study methodology and data display: multiple testing; potential for type I error; handling of heterogeneity of results and the use of randomeffects models throughout; method of quality assessment; and data display in forest and funnel plots.…”
Section: Disclosure Of Conflict Of Interestsmentioning
confidence: 99%
“…We thank Zhao et al [1] for their careful reading of our recently published meta-analysis [2], in which we assessed the potential relationship between vitamin K antagonists (VKAs) and both bone mineral density and fracture risk, and for their thoughtful comments. The authors raise the following five concerns regarding study methodology and data display: multiple testing; potential for type I error; handling of heterogeneity of results and the use of randomeffects models throughout; method of quality assessment; and data display in forest and funnel plots.…”
Section: Disclosure Of Conflict Of Interestsmentioning
confidence: 99%
“…Meta-analysis may result in type I errors because of systematic errors (bias) or random errors (chance) resulting from sparse data and repeated significance testing when a meta-analysis is updated with new trials. In our study [2], we found that the use of VKAs was associated with an increased risk of fractures in prospective studies (relative risk 1.09, 95% confidence interval 1.01-1.18, P = 0.03, I 2 = 0%). With TSA, Zhao et al [1] confirmed our findings of incident fractures, as shown in their Fig.…”
mentioning
confidence: 79%
“…Vitamin K antagonists' use and fracture risk: results from a systematic review and meta-analysis: reply We thank Zhao et al [1] for their careful reading of our recently published meta-analysis [2], in which we assessed the potential relationship between vitamin K antagonists (VKAs) and both bone mineral density and fracture risk, and for their thoughtful comments. The authors raise the following five concerns regarding study methodology and data display: multiple testing; potential for type I error; handling of heterogeneity of results and the use of randomeffects models throughout; method of quality assessment; and data display in forest and funnel plots.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Shiraki et al (3) also documented that fracture risk was associated with serum ucOC but not with BMD in osteoporotic patients. A meta-analysis indicated that vitamin K antagonists increased the fracture risk, but did not affect BMD (23). Therefore, vitamin K status should be associated with fracture risk, independent of BMD.…”
Section: Discussionmentioning
confidence: 99%